A new species of the genus Calamaria H. Boie in F. Boie, 1827 (Squamata: Calamariidae) from Mizoram State, India - Lalremsanga, Hmar Tlawmte; Malsawmdawngliana, Fanai; Bal, Amit Kumar; Vabeiryureilai, Mathipi; Hruaia, Vanlal; Korolev, Alexey M.; Vogel, Gernot; Poyarkov, Nikolay A.; Nguyen, Tan Van (Zootaxa, 2026)
We describe a new species of the genus Calamaria from Mizoram State, Northeast India, based on a combination of morphological and molecular evidence. Calamaria mizoramensis sp. nov. is distinguished from its congeners by a unique combination of morphological characters, including: 8–11 enlarged maxillary teeth; rostral higher than wide; prefrontal shorter than frontal and contacting the first two supralabials; mental not in contact with anterior chin shields; dorsal scales in 13–13–13 rows, smooth throughout; a single preocular and postocular; four supralabials, with the 2nd and 3rd ones contacting the eye; five infralabials; six scales surrounding the paraparietal; 147–175 ventrals; 13–27 paired subcaudals; a relatively short tail (10.3–13.1% in males, 4.7–6.5% of total length), thick and nearly cylindrical, terminating in an obtuse tip; dark brown to blackish-brown, with three to six longitudinal rows of slightly paler or dark-edged scales forming indistinct stripes of variable clarity along the body and a faint pale nuchal ring; a yellow ventral surface with dark outer corners on the ventral scales; and a broad, distinct median black stripe on the ventral surface of the tail. Phylogenetic analysis of the mitochondrial cytochrome b gene suggests that the new species represents a deeply divergent lineage within the genus Calamaria, with sister relationships to a clade that includes the remaining species from Indochina and East Asia. The genetic divergence of the new species from all its congeners for which the homologous sequences are available is also very high (minimal uncorrected p-distance of 15.3%). The new species is currently known from montane evergreen forests of Mizoram State, India (from elevations of 670–1,295 m asl.). This discovery adds to the growing number of herpetological findings in the Indo-Burma biodiversity hotspot and reinforces the need to reassess the complex taxonomy of the genus Calamaria. In addition, we provide the first comprehensive and updated checklist of the herpetofauna of Mizoram State, documenting 169 species, including 52 amphibians and 117 reptiles.